The militant face of democracy liberal forces for good - Geis, Anna; Muller, Harald; Schornig, Niklas (Cambridge University Press, 2013)
The book thus integrates democratic peace and democratic war into one consistent theoretical perspective, emphasising the impact of national identity. The book concludes by arguing that all democracies have a 'weak spot' where they would be willing to engage militarily.